Reprogramming of iPSCs to NPCEC-like cells by biomimetic scaffolds for zonular fiber reconstruction - Tianhui Chen; Zhongxing Chen; Juan Du; Min Zhang; Zexu Chen; Qingyi Gao; Aodong Chen; Qinghao Meng; Yang Sun; Yan liu; Linghao Song; Xinyue Wang; et al. (Bioactive Materials)
Ectopia lentis (EL), characterised by impaired zonular fibers originating from non-pigmented ciliary epithelial cells (NPCEC), presents formidable surgical complexities and potential risks of visual impairment. Cataract surgery is the only treatment method for EL, but it leads to the loss of accommodative power of the lens post-operatively. Furthermore, the challenge of repairing zonular ligaments in situ remains a significant global issue. Ocular tissue and aqueous humour samples from patients with EL were subjected to RNA sequencing and Olink high-throughput proteomic analysis, revealing the downregulation of pathogenic genes (FBN1, MFAP2) and upregulation of secretory proteins (IL-12, MMP-1). The high expression of FBN1 and MFAP2 in NPCECs suggests their potential as candidates for zonular fiber construction; however, the limited availability of donor sources restricts the feasibility of NPCEC transplantation therapy. The reprogramming and directional differentiation of induced pluripotent stem cells (iPSC) to NPCEC was successfully achieved using the developed biomimetic scaffolds that mimic the microstructures of natural radial zonular fibers. Excitingly, the single injection of induced NPCEC-like cells significantly contributed to restoring and enhancing mechanical properties in zonular fiber structures in a rabbit model with EL. This proposed in situ iPSC-based regeneration technique might serve as an innovative therapeutic strategy for clinical EL patients, reduce the cataract surgery rate, and retain the adjustment capacity of inherent lentis.